Neonatal Antifungal Consumption Is Dominated by Prophylactic Use; Outcomes From The Pediatric Antifungal Stewardship: Optimizing Antifungal Prescription Study. Issue 12 (December 2019) - Ferreras-Antolín, Laura; Irwin, Adam; Atra, Ayad; Dermirjian, Alicia; Drysdale, Simon B.; Emonts, Marieke; McMaster, Paddy; Paulus, Stephane; Patel, Sanjay; Kinsey, Sally; Vergnano, Stefania; Whittaker, Elisabeth; et al.
Abstract : Background: Diagnostic challenges combined with the vulnerability of neonates to develop invasive candidiasis (IC) may lead to antifungal administration in the absence of IC. A modified point-prevalence study was performed to obtain an improved insight and understanding of antifungal prescribing in this specific patient population. Methods: Neonates and infants ⩽90 days of age receiving systemic antifungals from 12 centers in England were included. Data were collected prospectively during 26 consecutive weeks and entered into an online REDCap database. Results: Two hundred eighty neonates and infants were included, the majority ⩽1 month of age (68.2%). Prematurity was the commonest underlying condition (68.9%). Antifungals were prescribed for prophylactic reason in 79.6%; of those, 64.6% and 76.3% were extreme low birth weight infants and prematurely born neonates, respectively. Additional risk factors were present in almost all patients, but only 44.7% had ≥3 risk factors rendering them more susceptible to develop IC. Nonpremature and non extremely low birth weight premature infants only scored ≥3 risk factors in 32.6% and 15%, respectively. Fluconazole was the most common antifungal used (76.7% of all prescriptions), and commonly underdosed as treatment. The number of microbiologic proven IC was low, 5.4%. Conclusions: Neonatal antifungal prophylaxis is commonly prescribed outside the recommendations based on known risk profiles. Fluconazole is the main antifungal prescribed in neonates and infants, with underdosing frequently observed when prescribed for treatment. Number of proven IC was very low. These observations should be taken into consideration to develop a national pediatric Antifungal Stewardship program aiming to guide rational prescribing.